2018
DOI: 10.1001/jamainternmed.2018.4357
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Frequency of Organic Food Consumption With Cancer Risk

Abstract: IMPORTANCE Although organic foods are less likely to contain pesticide residues than conventional foods, few studies have examined the association of organic food consumption with cancer risk. OBJECTIVE To prospectively investigate the association between organic food consumption and the risk of cancer in a large cohort of French adults. DESIGN, SETTING, AND PARTICIPANTS In this population-based prospective cohort study among French adult volunteers, data were included from participants with available informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
9

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 48 publications
(59 reference statements)
4
90
0
9
Order By: Relevance
“…These included the Norwegian Mother and Child Cohort Study [55,56]; KOALA Birth Cohort [58][59][60]; ALLADIN study [61]; PELAIGE Mother-Child Cohort [62] and the EARTH study [52]. Two adult-only cohorts involved development of cancer incidence in the Million Women Study [65], and self-reported health factors in the Nutri-Net Santé Cohort Study [20,53,63,64]. A retrospective case-control study in a mother-child cohort was also included [57].…”
Section: Observational Cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These included the Norwegian Mother and Child Cohort Study [55,56]; KOALA Birth Cohort [58][59][60]; ALLADIN study [61]; PELAIGE Mother-Child Cohort [62] and the EARTH study [52]. Two adult-only cohorts involved development of cancer incidence in the Million Women Study [65], and self-reported health factors in the Nutri-Net Santé Cohort Study [20,53,63,64]. A retrospective case-control study in a mother-child cohort was also included [57].…”
Section: Observational Cohort Studiesmentioning
confidence: 99%
“…The Nutri-Net Santé group also investigated associations with cancer incidence in a cohort of 68,946 participants [53]. The group, followed for a mean of 4.6 years, report that after adjustment for confounders, high organic food scores were linearly and negatively associated with the overall risk of cancer (HR for Q4 vs Q1, 0.75; 95%CI, 0.63-0.88; p for trend = 0.001; absolute risk reduction, 0.6%; HR for a 5-point increase, 0.92; 95%CI 0.88-0.96).…”
Section: Adult Researchmentioning
confidence: 99%
“…Occupational exposure has been reported to be associated with a higher rate of NHL in several meta-analyses 1 , 2 , 3 , 4 , 5 and prospective studies. 6 , 7 More recently, a prospective study 8 showed an association of a higher frequency of organic food intake with decreasing risk of NHL. Three agents have been associated with NHL and classified as carcinogenic by the International Agency for Research on Cancer: glyphosate, malathion, and diazinon.…”
Section: Introductionmentioning
confidence: 99%
“…A healthy and balanced diet based on fruits and vegetables that contain high amounts of compounds with antioxidant properties can help reduce cell death in sick patients (Terry et al, 2001) and most importantly, consumption of these fruits and vegetables can prevent development of chronic-degenerative diseases (Hu, 2003;McCullough et al, 2003). A study carried out by Baudry et al (2018) showed an important decrease in cancer risk of French participants that had higher consumption of organic food. This study conducted from 2009 to 2016 considered nearly 70 000 people.…”
Section: Resultsmentioning
confidence: 99%